Muscle strengthening of knee extensors in hemiparetics: prospective and longitudinal study - Gomes, Wildja de Lima; Scalha, Thais Botossi; Bovi, Ana Carolina Nunes; Castro, Wagner de Mello e; Pennacchi, Amanda; Gomes, Gabriela Aparecida; Taranto, Mariana; Cacho, Enio Walker de Azevedo; Lima, Núbia Maria Freire Vieira (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Several attempts to reduce spasticity have been directed to stroke sufferers based on the historical view that spasticity is the major determinant of motor dysfunction and that its reduction results in improved function of the affected limb. Paresis is also recognized as a limiting factor in hemiparetic rehabilitation and has a negative impact on self-care, mobility, or up and down stairs due to slow activation of motor units and difficulty in producing adequate amount of muscle strength. In the treatment of spasticity, many therapeutic procedures have been used. Resisted exercises occur when there is load on the body segment distal to the muscle that develops muscle tension, occurs muscle shortening and an external force is overcome. Objective: The aim of this study was to analyze the results of isometric and isotonic strengthen program in the quadriceps muscles of the affected limb of patients with chronic hemiparesis secondary to stroke and to evaluate its effects on spasticity, motor function of the lower limb, balance and mobility. Methods: The participants were divided into three groups: isotonic strengthening, isometric strengthening and control group. It was applied the Ashworth scale, Fugl-Meyer Protocol, Time Up and Go test and Berg Balance Scale. Results: The isometric and isotonic strengthening program presented post-treatment variations, whereby only the isometry group showed improvement in balance. The control group did not show a significant improvement. There was no increase in the muscular tonus of the quadriceps or hamstrings immediately after the treatment. Conclusion: The selective muscle strengthening of the quadriceps resulted in an increase of the motor function, balance and mobility followed by a decrease or maintenance of the muscular tonus of the patients.